The ghost in the news room: the legacy of Kenya's 2007 post-election violence and the constraints on journalists covering Kenya's 2013 General Election. Issue 4 (2nd October 2017) - Weighton, Lisa; McCurdy, Patrick
ABSTRACT: Domestic journalists covering Kenya's 2013 General Election worked in an exceptionally challenging media environment; one which was significantly shaped by the 2007 election and post-election violence (PEV). Rooted in literature on peace journalism (PJ), we examine how the PEV of Kenya's 2007 presidential elections informed and shaped journalists' practice around the 2013 Kenyan General Election. The article is based on qualitative interviews with 16 Kenyan print journalists and editors at the Daily Nation and Standard newspapers as well as interviews with 6 Kenyan media specialists. Our analysis finds the 2007 PEV significantly constrained journalistic practice in three ways: first, journalists witnessed violence in 2007 which anchored their 2013 coverage; second, interviewees felt a 'collective guilt' at journalism's failure to provide responsible coverage in 2007 creating a 'culture of restraint' and third, journalists felt compelled to 'sanitize' potentially inflammatory language creating a tension between journalists' duty to inform and strong desire to avoid contributing to conflict. This article concludes by siding with a growing critical chorus of PJ scholars critiquing its often "individualist" approach and calling for greater attention towards structural factors such as perceived social constraints when conceptualizing and theorizing the agency of journalists working in post conflict environments.